(untitled) (Tempo e Argumento, 2021)
The main objective of this paper is to analyze the political path pursued by Viriato Francisco Clemente da Cruz (1928-1973) in the context of the African independence movements, more specifically Angola. As the founder of the Movimento Popular de Libertação de Angola (MPLA), he treaded a path of affinities and tensions with the African independence movements while in the diaspora. Beside the local, regional and global scenarios in which those movements merge and fission each other, and in addition to any labels or accusatory/celebratory designations assigned to Viriato da Cruz, and under the light of very specific disputes, we will seek to shed light on little-known aspects of his political life. Keywords: nationalism; anticolonialism; Angola; political trajectories.